Penyuluhan, Pelatihan dan Pendampingan Pembuatan Pestisida Nabati Daun Pepaya di Desa Sumber Ketempah - Hasanah, Uswatun; Sutrisno, Andri (LPPPM STAI Darul Hikmah Bangkalan, 2021)
Agricultural products from year to year continue to decline. One of the factors that affect the decline in agricultural yields is the presence of Plant Pest Organisms (OPT) so that control measures are needed. Chemical control is one of the most widely used pest control by farmers. However, there are many negative impacts from the use of chemical pesticides for both the environment and human health. The relatively expensive price of chemical pesticides adds to the problems for farmers, especially during the Covid-19 pandemic. Vegetable pesticides can be used as an alternative for pest control during the Covid-19 pandemic because apart from being cheap, they are also safe for the environment and human health. The method used is cuunseling, training, and mentoring with the sample used is youth from the village source of Ketempah. The purpose of this activity is to make Sumber Ketempah village agriculture better, independent, and sustainable. The results of the implementation of the work program are 1 liter of papaya leaf vegetable pesticides and applied to tobacco plants at a dose of 10 ml/l to control armyworm pests.